(untitled) (Research, Society and Development, 2021)
Fibromyalgia is a rheumatic syndrome that causes widespread chronic musculoskeletal pain for more than three months, the symptoms of which are pain in soft tissues such as muscles, tendons or ligaments. The aim of this review was to analyze studies that assessed the influence of resistance training on the health of women with fibromyalgia. This is an integrative review of studies published between 2016 and 2020. The search and selection of studies was carried out using the terms: fibromyalgia OR fibromyalgia syndrome AND women AND adults AND resistance training. The databases used in the search were Pubmed, SciELO, Virtual Health Library (VHL). Initially, 1.368 articles were identified. After applying the filter (studies published in the last 5 years), 838 articles were relevant, of which 604 were indexed in Pubmed and 234 in the VHL. Of these, 813 articles were excluded after reading titles and abstracts and 25 were selected for reading in full. Of this total, 14 articles were excluded with justification and 11 met the inclusion criteria. Resistance training was found to be an important non-drug method capable of mitigating the effects of fibromyalgia in adult women, contributing to the improvement of quality of life, physical and mental health. In this way, resistance training contributed to reducing pain and fatigue, improving physical conditioning, increasing strength and endurance, reducing depression, improving mood and quality of life in the domains related to physical, social, emotional, mental aspects and vitality.